PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE DANPERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA MASA YANG AKAN DATANG - ANUGRAH HENNY, LINTANG (Jurnal Akuntansi AKUNESA, 2017)
Abstract This research aims to analyze the effect of dividend payout ratio, leverage andsales growth on the future pfofitability in companies listed on the Indonesia StockExchange 2011-2016. This research is intended for potential investors to be usedas a consideration in making investment decisions. This research used purposivesampling with total sample 2011-2016 equal to 492 samples of firm at IndonesiaStock Exchange. The analysis method used is multiple linier regression analysis.The results showed that leverage and sales growth positively related to futureprofitability, meanwhile dividend payout ratio negatively related to futureprofitability. Keywords: future profitability, dividend payout ratio, leverage, sales growth